News spillovers in the sovereign debt market - Gande, Amar; Parsley, David C. (Journal of Financial Economics, 2005)
We study the effect of a sovereign credit rating change of one country on the sovereign credit spreads of other countries from 1991 to 2000. We find evidence of spillover effects; that is, a ratings change in one country has a significant effect on sovereign credit spreads of other countries. This effect is asymmetric: positive ratings events abroad have no discernable impact on sovereign spreads, whereas negative ratings events are associated with an increase in spreads. On average, a one-notch downgrade of a sovereign bond is associated with a 12 basis point increase in spreads of sovereign bonds of other countries. The magnitude of the spillover effect following a negative ratings change is amplified by recent ratings changes in other countries. We distinguish between common information and differential components of spillovers. While common information spillovers imply that sovereign spreads move in tandem, differential spillovers are expected to result in opposite effects of ratings events across countries. Despite the predominance of common information spillovers, we also find evidence of differential spillovers among countries with highly negatively correlated capital flows or trade flows vis-á-vis the United States. That is, spreads in these countries generally fall in response to a downgrade of a country with highly negatively correlated capital or trade flows. Variables proxying for cultural or institutional linkages (e.g., common language, formal trade blocs, common law legal systems), physical proximity, and rule of law traditions across countries do not seem to affect estimated spillover effects.